Contribution of airline F&B to passenger loyalty enhancement in the full-service airline industry - Heesup, Han; Lee, Kai Sean; Chua, Bee Lia; Sanghyeop, Lee (Taylor and Francis, 2020)
This study examined the role of airline food and beverage (F&B) performances, and how it affects full-service airline passengers’ loyalty generation processes. The roles of passengers’ cognitive and affective appraisals of flight experiences were considered, as well as the moderating role in-flight physical environment. 302 U.S. airline passengers were sampled and results from a structural equation modeling showed that the intricate interrelationships of airline F&B performances, cognitive appraisal of flight experiences, and affective appraisal of flight experiences were significantly supported. Moreover, a metric invariance test identified that in-flight physical environment played a significant moderating role.